2006
DOI: 10.1021/ol053136g
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Nanodiamonds Part 3:  Thiolation of Tertiary/Bridgehead Alcohols

Abstract: [reaction: see text] Treatment of acyclic as well as polycyclic tertiary mono- and dihydroxy hydrocarbon derivatives with thiourea in the presence of hydrobromic and acetic acid represents a convenient one-step route to the respective tertiary thiols and dithiols. This procedure was used for the preparation of diamondoid thiols of diamantane, triamantane, [121]tetramantane, and others that are prospective nanoelectronic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
64
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 34 publications
0
64
0
4
Order By: Relevance
“…Over the past two decades, SAMs of thiol-functionalized molecules on Au have emerged as one of the most convenient and widely used means for forming well-ordered films of small molecules 15 . With the recent success of site-specific functionalization of diamondoids [16][17][18][19][20] , it is now possible to use higher-diamondoids as molecular building blocks to yield materials with well-defined structures, including SAMs of higher-diamondoids. Self-assembled monolayers of adamantane-1-thiol, the smallest, most abundant, and most readily synthesized diamondoid, forms highly packed hexagonal layers on Au(111) reportedly with lower defect densities than alkane thiols, with a 7x7 reconstruction and 6.9 Å nearest neighbor distance [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, SAMs of thiol-functionalized molecules on Au have emerged as one of the most convenient and widely used means for forming well-ordered films of small molecules 15 . With the recent success of site-specific functionalization of diamondoids [16][17][18][19][20] , it is now possible to use higher-diamondoids as molecular building blocks to yield materials with well-defined structures, including SAMs of higher-diamondoids. Self-assembled monolayers of adamantane-1-thiol, the smallest, most abundant, and most readily synthesized diamondoid, forms highly packed hexagonal layers on Au(111) reportedly with lower defect densities than alkane thiols, with a 7x7 reconstruction and 6.9 Å nearest neighbor distance [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…H ighly efficient solar energy harvesting and trapping in photosynthesis relies on sophisticated molecular machinery built from pigment-protein complexes (1,2). Although the pathways and time scales of excitation energy transfers within and among these photosynthetic complexes are well studied, less is known about the precise mechanism responsible for the energy transfer.…”
mentioning
confidence: 99%
“…Treatment of 8 with NaSH-treated Amberlite, which is reportedly pertinent for some tertiary thiols, 14 was not As an alternative method, Schreiner has demonstrated that tertiary alcohols can be converted to the corresponding thiols by treatment with thiourea in the presence of hydrobromic and acetic acids and subsequent alkaline hydrolysis. 15 The thiolation of monoalcohol 7 gave thiol 9 along with a byproduct alkene 10 (Scheme 4). The selectivity was modified by lowering the temperature of the first step (Table 1), giving an optimal yield of 97% at 25 °C with no detectable formation of the alkene (entry 6).…”
Section: Introductionmentioning
confidence: 99%